Public Perceptions Can Guide Regulation of Public Facial Recognition - Kugler, Matthew (Science and Technology Law Review, 2024)
Facial recognition technology is changing how people pass through customs at airports, check in at schools, and move anonymously in public spaces. Yet despite these transformations, its use by the government is largely unregulated. This Article informs the policy and doctrinal debates about facial recognition by presenting a public attitudes perspective. These three novel empirical studies show the nuanced views that Americans hold about government use of facial recognition. The data reveal that people are generally comfortable with the government using facial recognition to investigate serious crimes, enhance the security of controlled spaces like airports and schools, and increase the efficiency of identity verification in some contexts. But people are often not comfortable with casual governmental facial recognition use in public spaces. This pattern of strong comfort for tailored uses persisted even when, in a second study, participants were primed with negative information about the accuracy of facial recognition. Here I explore the implications of these results for both current Fourth Amendment doctrine as well as future legislative reform, promoting a balanced approach that allows tailored use of facial recognition while regulating its purposes.